Value of Time Drives Operational Costs of Road Freight Transport Operators (RFTO): A Case Study in Zimbabwe - Tapiwa Christopher Mujakachi; Marian Tukuta; Maria Tsvere (International Journal of Supply Chain Management, 2023)
From a business viewpoint, freight transportation is a necessity in the globalized world we live in. Companies are becoming more dependent on goods from various different locations worldwide and the demand for coordinated transportation is increasing. The aim of the study was to ascertain if Road Freight Transport Sector in Zimbabwe respected the value of time aspect in their operations. Value of time is a sound principle that strategically propels the business into the future. Literature highly recommends the value of time concept for business success as a key to customer satisfaction and an international best practice. This was a quantitative study of the road freight transport sector across Zimbabwe with a population of 1256 registered companies and a randomly picked sample size of 384. A total of 384 questionnaires were distributed and 291 were retrieved, giving a response rate of 75.6%. The study findings indicate that value positively influence firm competitiveness. This implies that travel time and reliability influences company’s reputation, profitability, customer satisfaction and market share. Several empirical studies have reached similar findings (Chi, King-lok, Steven, 2012; Song et al, Gitae, 2017) that value of time has positive impact on firm competitiveness. Study also found that all the registered companies that took part in the research confirmed that the value of time phenomenon was alien to their business practices as they worked on assumptions. They also indicated a loss of business due to customer complaints. The study recommends policy formulation for companies that emphasizes standard operating procedures and good time management for firms to be competitive. The study results and interpretation show that value of time positively influences firm competitiveness. Results imply that if firms in the road freight sector conduct regulars servicing of their fleet, train their employees, plan routes properly, respond to their customers and manage risks there can remain competitive.